Tác động của sự tiếp nhận EWOM đến hành vi đặt dịch vụ lưu trú và vai trò điều tiết của niềm tin EWOM - Hoàng Thị Phương, Thảo; Trần Diệu, Hằng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2022)
Online consumer reviews provide a numerous amount of information for consumers to evaluate services before making a purchase. The authors use cognitive behavioral theory SOR to investigate the effect of information adoption in the context of electronic word of mouth (EWOM) on online accommodation booking behavior and the moderating role of trust in EWOM in predicting customer booking behavior. The study uses Structural Equation Modeling (SEM) with survey data from 412 customers who booked their accommodation on online travel agencies (OTA). The results show that EWOM adoption has a positive influence on booking behavior, customer attitude towards OTA and customer attitude towards accommodation service have a mediating role in the relationship between EWOM adoption on booking behavior, trust in EWOM has a moderating effect on the relationship between EWOM reception on booking behavior, thereby emphasizing the role of trust in the context of online services.
Keywords: Online word of mouth; EWOM; Trust in EWOM; Online customer behavior; SOR